Exploring country-level institutional arrangements on the rate and type of entrepreneurial activity - Stenholm, Pekka; Acs, Zoltan J.; Wuebker, Robert (Journal of business venturing, 2013)
This study introduces a novel multidimensional measure of the entrepreneurial environment that reveals how differences in institutional arrangements influence both the rate and the type of entrepreneurial activity in a country. Drawing from institutional theory, the measure examines the regulatory, normative, and cognitive dimensions of entrepreneurial activity, and introduces a novel conducive dimension that measures a country's capability to support high-impact entrepreneurship. Our findings suggest that differences in institutional arrangements are associated with variance in both the rate and type of entrepreneurial activity across countries. For the formation of innovative, high-growth new ventures, the regulative environment matters very little. For high-impact entrepreneurship an institutional environment filled with new opportunities created by knowledge spillovers and the capital necessary for high-impact entrepreneurship matter most.